SOCIAL PROBLEMS OF THE UZBEK SSR: CAUSES AND NATURE OF WORKERS PROTESTS (Scientific journal of the Fergana State University, 2023)
The present article reveals the causes of the solidarity absence in the different layers of the population of Turkistan region and the attitude of the local population to the October revolution. The protests of the working class against the Bolsheviks policy were covered on the basis of archival documents.